Nutritional status of hyperlipidemics elderly in Indonesia according to body mass lndex (study in four Indonesian big cities) (Faculty of Medicine Universitas Indonesia, 2005)
The objective of this study was to assess the nutritional status of hyperlipidemics elderly. A cross sectional study was undertaken in 4 big cities in Indonesia using multistage random sampling. The respondents were 656 hyperlipidemics and non hyperlipidemics elderly who were the subsample of 1261 sample of a larger population study. Data were collected through anthropometric measurements and biochemical blood analysis. To determine the nutritional status by Body Mass Index (BMI) the criteria used for elderly men and women are as follows, underweight BMI ≤ 18.5 kg/m2, normoweight BMI 18.5 - 24.9 kg/m2, overweight BMI 25 - 29.9 kg/m2, and obese BMI ≤ 30 kg/m2. To determine lipid status, the criteria used are as follows, hyperlipidemics elderly, those who had plasma total cholesterol ≥ 240 mg/dl and or triglycerides ≥ 200 mg/dl. Prevalence of hyperlipidemics in elderly women is higher then elderly men, 56.2% vs 47.0%. The BMI of hyperlipidemics is mostly overweight (60.4%) and obese (57.1%) for elderly men; and mostly normoweight (59.1%) and overweight (59.5%) for elderly women. The prevalence of hyperlipidemics among undernourished elderly men and women were also quite high, 38.7% and 31.6% respectively. (Med J Indones 2005; 14: 97-100) Keywords : BMI, hyperlipidemics, elderly